FORMATION AND DEVELOPMENT OF SUBMERGED AIR JETS (Journal of Mechanical Engineering, 2015)
An experimental investigation on submerged air jets was carried out in a 14×14 cm2 perspex columnwith a liquid height of 25 cm. Jets were generated by flowing air at different velocities through nozzles immersedat the bottom of a stagnant liquid pool. The diameters of the nozzles used were 1, 4 and 6 mm. The jet formationwas observed in three different liquids; namely, water, ethanol and glycerol. The jet formation velocity and jetlengths at different liquids and with different nozzles were measured by video recording and image processing.Two distinct regime transitions; bubbling to jetting and jetting to bubble plume were observed. The jet lengthincreased steadily with jet velocity. The nozzle size was found to affect both jet formation and jet length. Theproperties of liquid also affect the formation of jet.